Livestock responses to droughts and severe winter weather in the Gobi Three Beauty National Park, Mongolia - Begzsuren, S.; Ellis, J.E.; Ojima, D.S.; Coughenour, M.B.; Chuluun, T. (Journal of arid environments, 2004)
We investigated how both droughts and dzuds (severe winter weather) control livestock mortality in a non-equilibrium steppe ecosystem of Mongolia, Gobi Three Beauty National Park. These steppe ecosystems have developed under high interannual variability of rainfall and nomadic grazing systems. Interannual precipitation variation was 39%, with 128 mm mean annual precipitation. The effect of climate variability and extreme events on livestock mortality is a critical aspect for the Mongolian economy. Analysis of drought and precipitation variability on livestock mortality rate was not significantly influenced by the index of mean annual precipitation and annual winter temperature. Overall, unlike hot dry regions, pastoral livestock mortality in the cold dry regions was affected more by dzuds and annual growing seasonal rain than by droughts. Dzuds can be frequent events, occurring as often as once every 2 and 3 years within a decade. The average annual livestock mortality for the combined drought and dzuds years (18%) was 4.8% greater than the years with dzuds alone, and 7% greater than in years with only drought. Thus livestock mortality appears to be more sensitive to dzuds than to droughts, and that dzuds contributes more to livestock mortality even years where combined drought and winter storms occur.